2017
DOI: 10.1212/wnl.0000000000004285
|View full text |Cite
|
Sign up to set email alerts
|

Developing an outline for teleneurology curriculum

Abstract: The emerging field of teleneurology is delivering quality care to neurologic patients in increasingly numerous technologies and configurations. Teleneurology is well-positioned to address many of the logistical issues neurologists and their patients encounter today. However, formalized medical training has not caught up with this developing field, and there is a lack of formal education concentrating on the specific opportunities and challenges of teleneurology. Considering this, the American Academy of Neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 15 publications
0
30
0
6
Order By: Relevance
“…62 Neuromuscular clinics and information about incorporation of trainees are underrepresented in the limited data about outpatient telemedicine in neurology. 63,64 Resources and telemedicine references have been created by numerous professional societies including the American Academy of Neurology and the American Association for Neuromuscular and Electrodiagnostic Medicine.…”
Section: Rapid Integration Of Telemedicinementioning
confidence: 99%
“…62 Neuromuscular clinics and information about incorporation of trainees are underrepresented in the limited data about outpatient telemedicine in neurology. 63,64 Resources and telemedicine references have been created by numerous professional societies including the American Academy of Neurology and the American Association for Neuromuscular and Electrodiagnostic Medicine.…”
Section: Rapid Integration Of Telemedicinementioning
confidence: 99%
“…The 2015-2016 Liaison Committee on Medical Education Annual Medical School Questionnaire reported that over a quarter of US medical schools have implemented telehealth training in their preclinical curriculum and nearly half have implemented it in their clinical curriculum [7]. However, much of the existing literature on telehealth for learners focuses on residents [3,8,9] or telehealth curricular descriptions for medical students [7,[10][11][12][13]. There is limited but growing literature on integrating medical students into telehealth visits [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature on telehealth education, over a quarter of medical schools delivered preclinical telemedicine curricula, and almost half provided clinical exposure through routine practice or telehealth electives. 3 Other specialties, such as dermatology, 4,5 psychiatry, 6 and neurology, 7,8 have reported telemedicine training for residents and fellows. There are a few reports of primary care telehealth training, with limited uses of telehealth technologies.…”
Section: Introductionmentioning
confidence: 99%